Differential effects of proteins and carbohydrates on postprandial blood pressure-related responses. Issue 4 (28th August 2014) - Teunissen-Beekman, Karianna F. M.; Dopheide, Janneke; Geleijnse, Johanna M.; Bakker, Stephan J. L.; Brink, Elizabeth J.; de Leeuw, Peter W.; Serroyen, Jan; van Baak, Marleen A.
<x content-type="archive" xml:space="preserve">Abstract</x> Diet composition may affect blood pressure (BP), but the mechanisms are unclear. The aim of the present study was to compare postprandial BP-related responses to the ingestion of pea protein, milk protein and egg-white protein. In addition, postprandial BP-related responses to the ingestion of maltodextrin were compared with those to the ingestion of sucrose and a protein mix. We hypothesised that lower postprandial total peripheral resistance (TPR) and BP levels would be accompanied by higher plasma concentrations of nitric oxide, insulin, glucagon-like peptide 1 (GLP-1) and glucagon. On separate occasions, six meals were tested in a randomised order in forty-eight overweight or obese adults with untreated elevated BP. Postprandial responses of TPR, BP and plasma concentrations of insulin, glucagon, GLP-1 and nitrite, nitroso compounds (RXNO) and S-nitrosothiols (NOx) were measured for 4 h. No differences were observed in TPR responses. Postprandial BP levels were higher after the ingestion of the egg-white-protein meal than after that of meals containing the other two proteins (P≤ 0·01). The ingestion of the pea-protein meal induced the highest NOx response (P≤ 0·006). Insulin and glucagon concentrations were lowest after the ingestion of the egg-white-protein meal (P≤ 0·009). Postprandial BP levels were lower after the ingestion of the maltodextrin meal than after that of the protein mix and sucrose meals (P≤ 0·004), while postprandial insulin concentrations were higher after the ingestion of the maltodextrin meal than after that of the sucrose and protein mix meals after 1–2 h (P≤ 0·0001). Postprandial NOx, GLP-1 and glucagon concentrations were lower after the ingestion of the maltodextrin meal than after that of the protein mix meal (P≤ 0·008). In conclusion, different protein and carbohydrate sources induce different postprandial BP-related responses, which may be important for BP management. Lower postprandial BP levels are not necessarily accompanied by higher NOx, insulin, glucagon or GLP-1 responses.